Application of airborne photogrammetry for the visualisation and assessment of contamination migration arising from a Fukushima waste storage facility. (March 2018) - Connor, D.T.; Martin, P.G.; Smith, N.T.; Payne, L.; Hutson, C.; Payton, O.D.; Yamashiki, Y.; Scott, T.B.
Abstract: Airborne systems such as lightweight and highly portable unmanned aerial vehicles (UAVs) are becoming increasingly widespread in both academia and industry - with an ever-increasing range of applications, including (but not limited to), air quality sampling, wildlife monitoring and land-use mapping. In this work, high-resolution airborne photogrammetry obtained using a multi-rotor system operating at low survey altitudes, is combined with ground-based radiation mapping data acquired at an interim storage facility for wastes removed as part of the large-scale Fukushima clean-up program. The investigation aimed to assess the extent to which the remediation program at a specific site has contained the stored contaminants, as well as present a new methodology for rapidly surveying radiological sites globally. From the three-dimensional rendering of the site of interest, it was possible to not only generate a powerful graphic confirming the elevated radiological intensity existing at the location of the waste bags, but also to also illustrate the downslope movement of contamination due to species leakage from the large 1m 3 storage bags. The entire survey took less than 1 h to perform, and was subsequently post-processed using graphical information software to obtain the renderings. The conclusions within this study not only highlight the usefulness of incorporating three-dimensional renderings within radiation mapping protocols, but also conclude that current methods of monitoring these storage facilities in the long term could be improved through the integration of UAVs within the standard protocol. Graphical abstract: Highlights: Airborne photogrammetry of Fukushima waste storage site. 3D rendering of site produced. Radiation map overlain onto model of study site. Contamination migration identified and modelled. Abstract : UAV photogrammetry and novel ground-based radiation mapping systems are used to quantify the success to which contaminated soil is isolated from the environment within the Fukushima clean-up.